2020
DOI: 10.1038/s41598-020-59735-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical selection of biomarkers for tumor-targeted image-guided surgery of myxofibrosarcoma

Abstract: Myxofibrosarcoma(MFS) is the most common soft tissue sarcoma(STS) in elderly patients. Surgical resection remains the main treatment modality but tumor borders can be difficult to delineate with conventional clinical methods. Incomplete resections are a common problem and local recurrence remains a clinical issue. A technique that has shown great potential in improving surgical treatment of solid tumors is tumor targeted imaging and image-guided surgery with near-infrared fluorescence. To facilitate this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
(59 reference statements)
2
26
0
Order By: Relevance
“…The presence of the biomarker in STS samples, regardless of the percentage of positive tumor cells, was determined on both tumor and stromal cells for TEM1. In STS, 77% (range 55–100%, n = 768) of the samples showed presence of TEM1 on average, reported in 4 different articles [ 26 , 27 , 28 , 29 ]. Staining was performed in 17 subtypes of STS ( Appendix C ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of the biomarker in STS samples, regardless of the percentage of positive tumor cells, was determined on both tumor and stromal cells for TEM1. In STS, 77% (range 55–100%, n = 768) of the samples showed presence of TEM1 on average, reported in 4 different articles [ 26 , 27 , 28 , 29 ]. Staining was performed in 17 subtypes of STS ( Appendix C ).…”
Section: Resultsmentioning
confidence: 99%
“…In MFS it was demonstrated that TEM1 was present in all 34 investigated samples, with a diffuse pattern of expression [ 27 ]. Staining was negative or very limited in normal adjacent tissue such as muscular fascia and peripheral nerve bundles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations